Ketentuan Pasal 93 Undang-Undang Nomor 6 Tahun 2018 Tentang Kekarantinaan Kesehatan Ditinjau Dari Hukum Pidana Indonesia - Suparmin, Entol; Miharja, Marjan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The provisions of Article 93 of Law number 6 of 2018, concerning Health Quarantine". the normative method is carried out on theoretical matters, knowing the provisions of article 93 of law number 6 of 2018, concerning health quarantine. Conclusion of Article 93: "Everyone who does not comply with the implementation of Health Quarantine as referred to in Article 9 paragraph (1) and/or obstructs the implementation of Health Quarantine so as to cause a Public Health Emergency shall be punished with imprisonment for a maximum of 1 (one) year and/or a maximum fine of Rp. 100,000,000.00 (one hundred million rupiahs)". But in the context of the development of criminal law in Indonesia, by giving place to living law or unwritten law. This research is expected to be able to become legal material that can contribute to the formation and application of criminal law in the administration of health and in enforcing the law in the Republic of Indonesia, so that the purpose of the law is a legal certainty that is just and beneficial for a fair law which is the ideal noble nation of Indonesia which is based on Pancasila and the laws of the Republic of Indonesia (UUD NRI 1945).